Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/mph.0000000000001766
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vessel Analysis as a Novel Screening Tool to Identify Childhood Acute Lymphoblastic Leukemia Survivors at Risk of Cardiovascular Disease

Abstract: Azanan: Research investigation, data analysis and curation, data interpretation, manuscript writing, editing, data visualization, manuscript review and review and approval of final manuscript. Sudhashini Chandrasekaran: Research investigation, data analysis and curation, data interpretation, manuscript review and review and approval of final manuscript. Erda Syerena Rosli: Research investigation, manuscript review and review and approval of final manuscript. Chua Ling Ling: Research investigation, manuscript r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…All measures are calculated by vessel type (arteriole or venule) and region (zone, whole image, quadrants). VAMPIRE is a validated software application and has been extensively used in several international studies 36 38 39…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…All measures are calculated by vessel type (arteriole or venule) and region (zone, whole image, quadrants). VAMPIRE is a validated software application and has been extensively used in several international studies 36 38 39…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…Since the eye offers direct visualization of the retinal microcirculation, it is possible to non-invasively evaluate the retinal vasculature through high-quality imaging and the assistance of reliable and validated software, and, consequently, visualize damage to the microcirculation in vivo. The vascularization of the retina can be easily observed using fundus photography, video recording, and tomographic technology, which is becoming a useful screening tool for cerebrovascular and cardiovascular diseases, given that several studies have demonstrated a correlation between the calibers of the retinal vessels and cardiovascular risk [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to measure the prevalence of frail and prefrail phenotype in our multiethnic (ethnically diverse, single-center representative) Asian cohort of young adult survivors of childhood leukemia in comparison to their age-matched and sex-matched peers. In our earlier studies, we reported that the childhood ALL survivors were at higher risk for cardiometabolic conditions 15,16 and had evidence of dysregulated immune system such as elevated inflammatory biomarkers and increased circulating activated T cells 17 . Studies in elderly populations have shown that frailty is associated with metabolic conditions, 18,19 as well as chronic low-grade inflammation and an altered T-cell phenotype; a constellation of conditions known as “inflammaging.” Hence, we also examined the association between frailty phenotype with immune and metabolic derangements in our cohort of childhood ALL survivors with the aim of identifying potential areas for intervention.…”
mentioning
confidence: 99%